Cultivating Critical Thinking in History Education through Problem-Based Learning: A Case Study from Post-Colonial Indonesia - Destiana Safitri; Arif Purnomo; Ganda Febri Kurniawan; Dimas Anggoro (Indonesian Journal of History Education, 2026)
Abstract: This study critically examines the cultivation of critical thinking skills through Problem-Based Learning in history education at SMA Negeri 2 Kebumen, Indonesia. Drawing on qualitative case study methodology, the research investigates how PBL implementation shapes students' critical thinking development across twelve indicators derived from Ennis's critical thinking framework. The findings reveal that while students demonstrated competency in eight indicators including focusing questions, analysing arguments, and interacting with others, four indicators remained underdeveloped: deduction and induction, defining terms, and identifying assumptions. This study argues that PBL's effectiveness in history education depends significantly on teacher facilitation quality, student readiness, and the extent to which critical thinking is explicitly taught rather than assumed to develop incidentally. The research contributes to international conversations about active learning pedagogies in post-colonial history education contexts, highlighting both the potential and limitations of PBL for developing historical thinking competencies.   Abstrak: Studi ini mengkaji secara kritis penumbuhan keterampilan berpikir kritis melalui Problem-Based Learning (PBL) dalam pendidikan sejarah di SMA Negeri 2 Kebumen, Indonesia. Dengan metodologi studi kasus kualitatif, penelitian menyelidiki implementasi PBL terhadap dua belas indikator berpikir kritis dari kerangka Ennis. Temuan menunjukkan siswa kompeten pada delapan indikator, seperti memfokuskan pertanyaan dan menganalisis argumen, namun empat indikator lain masih kurang berkembang, yakni deduksi dan induksi, pendefinisian istilah, serta identifikasi asumsi. Studi berargumen bahwa efektivitas PBL bergantung pada kualitas fasilitasi guru, kesiapan siswa, dan pengajaran eksplisit berpikir kritis. Penelitian ini berkontribusi pada wacana pedagogi aktif dalam konteks sejarah pascakolonial, menyoroti potensi dan keterbatasan PBL.